Analysis Of Nursing Care In Schizophrenic Patients With Chronic Low Self-Esteem Through Hortikultural Therapy At Rsj Prof. Dr. Soerodjo Magelang - Revi Nur Ristanti (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Background : Schizophrenia is a severe mental disorder that is chronic and requires antipsychotic treatment for a long time or even a lifetime (Julacha et al. 2022). One of the nursing problems in Schizophrenic patients encountered is low self-esteem. Low self-esteem is a personal assessment of the results achieved by analyzing how far the behavior meets the ideal self. Long-lasting low self-esteem in the absence of therapeutic intervention can lead to identity chaos and eventually personalization. So it is necessary to make a promotive effort.Purpose : To explain the application of horticultural therapy to improve self-esteem in schizophrenic patients with chronic low self-esteem.Method : Using a case study of the application of horticultural therapy in 3 patients with chronic low self-esteem. The location of the case study was carried out at Wisma Dwarawati RSJ Prof. Dr. Soedjono Magelang. Selection of case study subjects according to inclusion criteria. Data collection was carried out through a therapeutic approach to patients, observation, and measurement of low self-esteem levels using the Rosenberg Self Esteem Scale (RSES) instrument. Implementation was carried out for three meetings for 60 minutes.Discussion : Based on research by Krissanti et al. (2019) revealed that occupational gardening therapy can reduce the level of low self-esteem disorders. Recommendations : Efforts in implementing low self-esteem patients with horticultural therapy can affect the level of self-esteem in patients to fall. So that it can be used as a guideline for health workers to provide implementation of structural activity therapy with horticultural therapy in patients with intense chronic low self-esteem.Keywords : Schizophrenia, Low Self-Esteem, Horticultural Therapy